DO SUPPLY‐SIDE FORCES EXPLAIN GEOGRAPHIC VARIATION IN HEALTH CARE USE?. (24th July 2020) - Callison, Kevin; Kaestner, Robert; Ward, Jason
Abstract : Regional variation in health care utilization has been well‐documented, yet uncertainty persists about whether this variation is primarily the result of supply‐side or demand‐side forces. We provide new evidence on this issue by examining changes in health care use for the near‐elderly as they transition from being uninsured into Medicare. Results support a causal, supply‐side explanation of regional variation. Estimates indicate that gaining Medicare coverage in above‐median spending regions increases the probability of at least one hospital visit by 40% and the probability of having more than five doctor visits by 26% relative to similar individuals in below‐median spending regions. ( JEL D43, H42, H51, I1, I11, I13)